Transcatheter Tricuspid Valve-in-Valve Replacement Using a J-Valve System for a Failed Tricuspid Bioprosthesis - Mingkui Zhang; Hui Xue; Lifu Miao; Xiujie Tang; Yanbin Shao (Case Reports in Cardiology)
Background. Redo operation for failed tricuspid bioprosthetic valves is associated with high morbidity and mortality. Transcatheter tricuspid valve-in-valve implantation has become an acceptable option for high-risk patients with a failed tricuspid bioprosthesis. We present a case of successful tricuspid valve-in-valve implantation using a J-valve in a failed tricuspid bioprosthesis position. Case Summary. A 48-year-old male, who had a failed tricuspid bioprosthesis, presented with right-side heart failure, right-to-left shunting at the atrial level, severe dyspnea, cyanosis, peripheral edema, hepatauxe, and ascites. After the interdisciplinary assessment, we successfully performed transcatheter tricuspid valve-in-valve implantation with the J-valve system. At 34-month postoperative follow-up, the patient had no symptoms of heart failure and the echocardiogram showed good valve position and well hemodynamic status. Conclusions. This case demonstrated that the J-valve system may be a new option for high-risk patients with a failed tricuspid bioprosthetic valve.